DPSIR MODEL AS A TOOL TO ASSES LAND CONVERSION TARIFF POLICY IN YOGYAKARTA - Nina Novira; Syarifah Aini Dalimunthe; Aditya Pandu Wicaksono; Nur Indah Sari Dewi; Triana Sefti Rahayu (Jurnal Kependudukan Indonesia, 2015)
Land use change from agricultural land to non-agricultural purposes in Yogyakarta Special Province (DIY) is the main factor leading to the decrease of agricultural land. The increasing population growth has led to a higher demand for land, which is contributing to the rapid land use changes. Land scarcity has led to a change in land utilization within the city and in the surrounding area. The DPSIR Model is used as the basis for the impact assessment analysis on the tariff policy implementation regarding to the controlling of the land use change. Driving force in this model is migration and the pressure is land use change. The state is divided into three categories, state of economic dimension, environmental dimension, and social dimension. These have caused impacts on land degradation, threats to food security, and pollution. As the response to this, the government introduced the policy PERDA No. 53 Year 2007 about authorizing land use in DIY. This paper is intended to explain how the DPSIR model is used to assess the policy implementation.